Examining the Impact of Acceptance and Commitment Therapy Intervention on Perceived Stress, Cortisol Levels, and Heart Rate Variability Among Athletes - Pellikka, Venla (2024)
Pellikka, V. 2024. Examining the Impact of Acceptance and Commitment Therapy Intervention on Perceived Stress, Cortisol Levels, and Heart Rate Variability Among Athletes. Faculty of Sport and Health Sciences, University of Jyväskylä. Master´s Thesis in Sports Coaching and Fitness Testing. 55 p., 7 attachments.